Mobility and material culture in the Middle Mesolithic of Fennoscandia – validating the input from biomolecular studies - Skar, Birgitte (The University of Bergen, 2022)
Similarities in late-glacial lithic technology (direct percussion) of western Europe and the oldest counterparts of Scandinavia appearing around 11,700 BP have sustained arguments for an early postglacial migration from northwestern Europe into Scandinavia including coastal areas of northern Norway. However, another lithic technology (pressure blade), occurring in Fennoscandia around 10,300 BP, indicates contacts with groups in the east and potentially a second and east-west migration deriving from the Russian mainland. aDNA studies of some of the oldest coastal human individuals from Europe, represented by two Norwegian skeletons (9500 BP) unveiled admixture of southern hunter gatherer (SHG) and eastern hunter gatherer (EHG), descended from isolated Glacial refugia. The Norwegian samples show dominance of EHG while contemporary samples from Gotland show a dominance of SHG ancestry. Isotopic markers of a diet consisting of more than 80% marine protein deriving from the highest level of the food chain sustain the importance and likely attraction of marine mammal resources. The biomolecular results underpin a second migration into Norway from northeast c. 10,300 BP, likely over the Cap of the North. Recent lithic studies covering larger parts of Central Scandinavia and Russia, however, provide a more fine-tuned narrative of networks and pulses of migration.